Percutaneous Cholecystostomy: A Bridge to Less Morbidity - Anil Kumar Singh (The Arab Journal of Interventional Radiology)
Percutaneous cholecystostomy (PC) is a minimally invasive procedure for decompressing gall bladder (GB) or biliary system in emergency settings, performed in patients with GB or biliary diseases who are at high risk for surgical exploration. Indications range from acute cholecystitis in seriously ill patients to overdistended GB with impending perforation to overt GB perforation. This procedure, by allowing biliary drainage, helps in controlling the infection and optimizing the patient's condition for definitive treatment in the form of elective surgery if possible, thus acting as a bridge to a definitive treatment option. In some cases, such as acute acalculous cholecystitis, it may obviate the need for surgery, and in malignant biliary obstruction, it may be used as a palliative measure to keep GB decompressed. This review article focuses on and revisits many aspects of PC including technical aspects, clinical indications, outcomes, and safety of the procedure, in addition to its role as bridge therapy versus definitive therapy versus palliative option. It includes observations based on the author's own work experience and review of the literature.